2008
DOI: 10.1364/ol.33.002500
|View full text |Cite
|
Sign up to set email alerts
|

Planar waveguide-coupled, high-index-contrast, high-Q resonators in chalcogenide glass for sensing

Abstract: High-index-contrast, compact microdisk resonators in thermally evaporated As 2 S 3 and Ge 17 Sb 12 S 71 chalcogenide glass films are designed, fabricated using standard UV lithography and characterized. Our pulley coupler configuration demonstrates coupling of the resonators to monolithically integrated photonic wire waveguides without resorting to demanding fine-line lithography. Microdisk resonators in As 2 S 3 support whisperinggallery-mode with cavity quality factors (Q) exceeding 2 × 10 5 , the highest Q … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 114 publications
(72 citation statements)
references
References 18 publications
1
70
1
Order By: Relevance
“…Compared to the conventional coupler configuration, the pulley coupler design improves the fabrication tolerance by increasing the coupling strength [78]. Figure 4a shows the TE polarization transmission spectrum of the resonator.…”
Section: Integrated Photonics For Infrared Spectroscopic Sensingmentioning
confidence: 99%
“…Compared to the conventional coupler configuration, the pulley coupler design improves the fabrication tolerance by increasing the coupling strength [78]. Figure 4a shows the TE polarization transmission spectrum of the resonator.…”
Section: Integrated Photonics For Infrared Spectroscopic Sensingmentioning
confidence: 99%
“…Thus the group of Luther-Davies has reported postprocessing problems of crystallization of As-S rib waveguides which had been formed in thermally evaporated As-S films on a substrate of oxidized Si. 33 In addition, Hu et al 34 reported that they coated thermally evaporated As-S with SU8 polymer to "prevent surface oxidation of devices in As-S." Moreover, Hu et al 15 postheat-treated waveguides to "stabilize the glass structure." Yet no such problems were reported when they applied similar processing to form Ge-Sb-S rib waveguides, in which, purposefully, no additional upper cladding layer was added.…”
Section: During Manufacturementioning
confidence: 99%
“…Subsequent device fabrication on ChG films were performed using lift-off 15 or thermal nanoimprint [16][17][18] . Both methods are capable of generating sub-micron single-mode optical waveguides.…”
Section: Materials Synthesis and Device Fabrication Protocolsmentioning
confidence: 99%